TINJAUAN YURIDIS TERHADAP TINDAK PIDANA PENIPUAN SECARA ONLINE BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2008 JO UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Devi Trisnawati (Bajang Institute, 2023)
The development of the current era allows all conveniences to be accessed. Including convenience in the world of business economics. This is supported by the presence of electronic transaction methods that make business activities much younger. Although it has positive values, in reality, electronic transactions also have a positive side in the form of being prone to online fraud. Therefore, this research is conducted to be a reference as a warning that fraud can occur through online transactions. The research method of this writing uses the juridical analysis method by analyzing Law Number 11 of 2008 jo Law Number 19 of 2016 concerning Information and Electronic Transactions. The result is that the criminal act of fraud through electronic payments (online) in realizing legal protection is Article 378 of the Criminal Code which regulates the criminal act of fraud, also specifically regulated in Article 28 paragraph (1) jo Article 45A paragraph (1) of Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions which regulates the criminal act of fraud committed through electronic transactions and is punishable by a maximum sentence of 6 (six) years and / or a maximum fine of Rp 1,000,000,000.00 (one billion rupiah).